The Effect of Using Chain Writing Method to Teach Writing Recount Text (A Quasi Experimental Research at Class X MIPA of MAN 5 Jombang) - Purwanto, As Syifa Zulqarnaın (English Education Study Program, 2023)
This quasy experimental research aimed to find out whether there is a significant effect of chain writing method on students' writing skill of Recount Text in X MIPA 1 of MAN 5 Jombang. Class X MIPA 1 was chosen as the sample by using cluster random sampling. t-test was conducted to compare the students' writing score before and after the treatment and to analyze the hypotheses. the result shows that Sig. (2- tailed) is 0.000. The result of Sig. (2- tailed) 0.000 is lower than alpha value 0.05. It can be concluded that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted which means there is significant improvement of using Chain writing method in students’ writing Recount Text in class X MIPA 1 MAN 5 Jombang the academic year of 2022/2023. Overall it can be concluded that teaching writing Recount Text by using Chain writing method of nine grade of X MIPA 1 MAN 5 Jombang is proved to influence students’ writing skill. Based on the research findings, it is suggested that chain story can be used by teachers in teaching writing recount text.